Measurements of hydrogenated titanium by electric methods; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Larionov V. V. Vitaliy Vasilyevich (High energy processes and external exposure of materials, 2016)
Title screen